Effects of Different Extraction Methods on Antioxidant Properties and Allicin Content of Garlic - Somayyeh, Loghmanifar; Leila, Roozbeh Nasiraie; Hamidreza, Nouri; Sara, Jafarian (Journal of Food Science and Hygiene, 2020)
The ever-present need for human communities to extract herbal active ingredients has necessitated many studies to be carried out in order to introduce more efficient and cost-effective extraction processes. The traditional extraction methods are very time consuming and use large volumes of solvents. The large volumes of solvents consumed in such methods not only increase costs but also pose many environmental problems. New extraction methods have been recently introduced to replace the traditional ones. These new methods reduce the volumes of required solvents, shorten the process and increase its efficiency and improve the quality of the products. In this study, the three methods of immersion, boiling, and ultrasound using water/ethanol solvents were employed for garlic extraction and compared with each other in terms of the extraction speed and time, the antioxidant property of the extract, and the quantity of the heat-sensitive active ingredient. The results showed that the highest allicin content (0.086%) was observed in the ultrasonic aqueous extract. The largest amounts of phenolic compounds (0.311 mg gallic acid equivalent) were observed in the ultrasonic aqueous extract followed by the aqueous extract prepared after 72 h in a shaking incubator. The highest inhibition rate (50% at 5000 ppm) was that of the ultrasonic aqueous extract and the shaken aqueous extract. Other extracts achieved an inhibition rate of 50% at 8000 ppm. Therefore, ultrasonic extraction can be a good alternative to traditional extraction methods.